Assessment of LeadCare® II analysis for testing of a wide range of blood lead levels in comparison with ICP–MS analysis. (May 2021) - Nakata, Hokuto; Nakayama, Shouta M.M.; Yabe, John; Muzandu, Kaampwe; Toyomaki, Haruya; Yohannes, Yared Beyene; Kataba, Andrew; Zyambo, Golden; Ikenaka, Yoshinori; Choongo, Kennedy; Ishizuka, Mayumi
Abstract: The LeadCare® testing system, which utilizes anodic stripping voltammetry (ASV) methodology, has been widely used worldwide for cost-effective blood lead level (BLL) screening. However, some concerns have recently been issued regarding inaccurate results obtained using LeadCare®. Hence, we aimed to evaluate the accuracy of BLL measured by LeadCare® II (BLLLC ) by comparison with ICP-MS (BLLIM ) by the Passing–Bablok regression, Deming regression, and Bland–Altman analyses by using 994 venous blood samples. BLLLC ranged from 3.3 to 162.3 μg/dL, while BLLIM ranged from 0.8 to 154.8 μg/dL. Although BLLLC and BLLIM exhibited a strong and positive correlation, BLLLC values were generally greater than BLLIM values, indicative of the overestimation of the LeadCare® analysis. A large positive bias of 19.15 ± 8.26 μg/dL and 29.25 ± 14.04 μg/dL for BLLLC compared with BLLIM were recorded in the BLLLC range of 45.0–64.9 μg/dL and for ≥65.0 μg/dL, respectively. In contrast, a bias of ≤0.3 μg/dL was observed at a BLLLC of less than 10.0 μg/dL. Blood copper, cadmium, and iron levels did not exhibit an effect on the bias of BLLLC, indicative of the minimal potential interferences of the metals; these interferences are a cause for concern with the ASV method. In conclusion, LeadCare® analysis is thought to be a good tool for screening purposes at a lower BLL around the reference level of 5 μg/dL in the initial stage; however, conversion or retesting using a laboratory analyzer is recommended at a higher BLL for appropriate clinical evaluation and research. Highlights: Comparison between blood lead levels measured by LeadCare II and ICP-MS. 994 venous blood samples compared by three different statistical comparison methods. Large positive bias of LeadCare II compared to ICP-MS at the levels above 45 μg/dL. No intermetallic interferences of blood copper, cadmium and iron. Conversion or retesting using a laboratory machine is recommended at a higher level.